2015
DOI: 10.1039/c5ta01058f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient solar hydrogen production from neutral electrolytes using surface-modified Cu(In,Ga)Se2photocathodes

Abstract: The effects of a phosphate buffer electrolyte and surface modification with thin conductor layers on the photoelectrochemical properties of CdS and Pt-modified polycrystalline Cu(In,Ga)Se 2 (CIGS) photocathodes were investigated. The photocurrent obtained from Pt/CdS/CIGS electrodes, in which the CIGS layer was fabricated by co-evaporation using a three stage method, clearly increased in a phosphate buffer electrolyte solution as a result of promotion of the hydrogen evolution reaction. The half-cell solar-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
134
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(150 citation statements)
references
References 48 publications
13
134
0
3
Order By: Relevance
“…It should be noted that the Pt/CdS/CuGa3Se5/AgxCu1−xGaSe2 photocathode produced hydrogen stably for over 19 days. A large leap in maximum photocurrent and HC-STH was achieved using a surface-modified CIGS-based photocathode with thin conductor layers employing a neutral phosphate buffer solution as an electrolyte [47]. This suggested that a conductor layer such as titanium and molybdenum prevents the formation of a Schottky barrier between Pt and CdS.…”
Section: Hydrogen Evolution From Water Using Copper Chalcopyrite Photmentioning
confidence: 99%
“…It should be noted that the Pt/CdS/CuGa3Se5/AgxCu1−xGaSe2 photocathode produced hydrogen stably for over 19 days. A large leap in maximum photocurrent and HC-STH was achieved using a surface-modified CIGS-based photocathode with thin conductor layers employing a neutral phosphate buffer solution as an electrolyte [47]. This suggested that a conductor layer such as titanium and molybdenum prevents the formation of a Schottky barrier between Pt and CdS.…”
Section: Hydrogen Evolution From Water Using Copper Chalcopyrite Photmentioning
confidence: 99%
“…Kumagai et al suggested that the Ti and Mo layers suppress Schottky barrier formation at the Pt/CdS interface, and enhance electron flow to the Pt. [19] The Ti layer forms an intimate contact with the CdS with a lower potential [8] and ZnSe. The VBM for ZnSe is obtained from PESA measurements (see Figure 2), and the bandgap is set to 2.7 eV.…”
mentioning
confidence: 99%
“…Indeed, a CIGSe/CdS/Pt photocathode generating an outstanding photocurrent density of ca. 25 mA cm −2 at applied potential of 0V versus RHE and a V OC of +0.65 V versus RHE under standard 1 Sun illumination and in a neutral pH electrolyte was reported [29]. Stronger driving force thanks to very negative conduction band edge potential of ca.…”
Section: Chalcopyrite-type Semiconductorsmentioning
confidence: 93%
“…8.0 mA cm −2 was achieved for a Cu 2 O photocathode [27,30] while that of ca. 25 mA cm −2 was recorded for a CIGS photocathode [29]. We note that even fill-factor (ff) is a critical parameter to appreciate the actually performance of a photoelectrochemical device, e.g.…”
Section: Current Achievements and Remained Technicalmentioning
confidence: 99%